Controle das propriedades estatísticas do campo e biestabilidade óptica em eletrodinâmica quântica de cavidades - Souza, James Alves de (2013)
We investigate in this thesis the control of absorptive optical bistability in a standing wave optical cavity filled with a collection of two and three-level noninteracting atoms weakly coupled to a single electromagnetic mode of a optical resonator. The observed control for the three-level configuration happens under cavity coherent population trapping conditions, it is sensitive to the induced atomic coherence in the system and it can be manipulated through different parameters. We propose some applications presenting a new effect, named by ourselves as complementary optical bistability. It is very interesting to exploit bistability phenomenon to perform bistable cascade devices, such as an optical transistor. We also study the all-optical control of the quantum fuctuations of a beam via a combination of single-atom cavity quantum electrodynamics (CQED) and electromagnetically induced transparency (EIT). Specifically, the EIT control field is used to tune the CQED transition frequencies in and out of resonance with the probe light. In this way, single-photon and two-photon blockade and anti-blockade effects are employed to produce sub-Poissonian and super-Poissonian light fields, respectively. The achievable quantum control paves the way towards the realization of a prototype of a quantum transistor which amplifies or attenuates the noise. Its feasibility is demonstrated by calculations using realistic parameters from recent experiments.